Possible origin of polymorphism for chromosome number in the assassin bug Zelurus femoralis longispinis (Reduviidae: Reduviinae) - Poggio, M.G. (2013)
In this study, we analysed a population of Zelurus femoralis longispinis polymorphic for chromosomal number. The fundamental karyotype of this subspecies is 2n=22=20A+XY (male), but individuals with 2n=23=20A+XY+extra chromosome have been found at high frequency and collected at different time periods. We examined male meiotic behaviour, average length as percentage of the sex chromosomes, the content, distribution and composition of heterochromatin, and the number and location of ribosomal DNA in the two cytotypes found. The meiotic behaviour of the extra chromosome was highly regular and similar to that of sex chromosomes. The average length of the sex chromosomes in individuals not carrying the extra chromosome was significantly greater than in those carrying it. The results support a hypothesis that the extra chromosome might have originated by fragmentation of the original X chromosome into two unequal-sized chromosomes (X1 and X2), leading to an X1X2Y multiple system. Maintenance of the polymorphism with time appears to indicate that the new chromosomal variant is neutral or at least not detrimental, or that it could be selectively advantageous. This polymorphic population represents direct evidence of a multiple sex chromosome system originating through fragmentation of a single X in Reduviidae as well as in Heteroptera. © 2013 The Linnean Society of London.